Sustainable investment strategies in a pandemic: a comparative study of Islamic and conventional mutual funds in Malaysia - Haider Mohammed Baniata; Mohammad Othman; Nawaf Abdallah Aljundi; Anas Ahmad Bani Atta; Ahmad Bani Ahmad; Ahmad A. I. Shajrawi; Laith T. Khrais (Discover Sustainability)
Abstract The goal of work is to analyze the differences and similarities in the money flows of Islamic (IMF) and conventional mutual funds (CMF) throughout two intense events: the global financial crisis (GFC), and the COVID-19 pandemic. Pandemics have been extremely uncommon. Therefore, this work offers novel guide on what effect a global infectious malady can have concerned mutual funds’ flow. The entire sample comprises 87 equity IMFs and 83 equity CMFs in Malaysia, encompassing the two crises from January 2005 to October 2020. This work uses panel regression analysis (fixed-effect and random effect). The main findings are both crises led to a decrease in the money flows for both IMFs and CMFs. The outcomes indicate that viral pandemics effect mutual funds, similar to the earlier financial crises. However, the impact of both crises was less on the flows of IMFs than on the flows of CMFs. The implications of this paper provide managers with an overall view about investors behaviour, especially during extreme events. Thus, it helps them to build their strategies based on the behaviour and preferences of investors. The implication to investors is that it allows investors to decide in directing their money to suitable funds, such as Islamic funds, especially during these extreme periods. This work`s novel contribution is that it’s the first research exploring the effect of the COVID-19 crisis as well as the financial crisis and fund flows in Malaysia.